Nanostructured Surface and Antimicrobial Properties of Chemically Modified Polymer Foils. Issue 14 (15th April 2019) - Knapova, Tereza; Matousek, Jindrich; Kolarova, Katerina; Slepicka, Petr; Sicha, Vaclav; Trogl, Josef; Kolska, Zdenka
Abstract: Surfaces of solid polymer foils were modified by chemical methods. Surfaces were firstly activated by Piranha solution and then grafted with selected amino‐compounds (cysteamine, ethylenediamine and chitosan). Next step was established of cobaltacarborane compound. Selected surface properties were studied using various available methods to characterize changes in surface chemistry (X‐ray photoelectron spectroscopy), charge and polarity (electrokinetic analysis), wettability (goniometry), surface roughness and morphology were studied by atomic force microscopy and scanning electron microscopy. Surface area with porosity by adsorption/desorption isotherms. The surface properties dramatically differ after individual activation and modification steps and can affect the adhesion properties. Also some antimicrobial tests were realized. Samples treated with cobaltcarborane compounds exhibit antimicrobial effects to algae D. quadricauda and to gram‐ positive bacteria S. epidermidis . It was confirmed this cobaltcarborane compound can be easily grafted on polymer surface by two ways (i) directly onto Piranha activated polymer surfaces and/or (ii) via amino‐ compounds previously grafted onto Piranha activated polymer surfaces. The most important fact is that its antimicrobial behaviour remains preserved also after its grafting onto polymer surface. These chemically modified polymers can be used in the fields of nanobiotechnology, tissue engineering studies, biomedicine or environment protection. Abstract : How important the nanostructured polymers are in everyday life? Surfaces of solid polymer foils were modified by chemical methods. Surfaces were firstly activated by Piranha solution and then grafted with selected amino‐compounds. Next step was established of cobaltacarborane compound. Selected surface properties were studied using various available methods to characterize changes in surface chemistry (X‐ray photoelectron spectroscopy), charge and polarity (electrokinetic analysis), wettability (goniometry), surface roughness and morphology were studied by atomic force microscopy and scanning electron microscopy. Surface area with porosity by adsorption/desorption isotherms. These chemically modified polymers can be used in the fields of nanobiotechnology, tissue engineering studies, biomedicine or environment protection.